Geochemistry of Non-Traditional Stable Isotopes - Albarède, Francis; Beard, Brian L.; Johnson, Clark M. (De Gruyter, 2018)
The goal for Volume 55 of Reviews in Mineralogy and Geochemistry was to bring together a summary of the isotope geochemistry of non-traditional stable isotope systems as is known through 2003 for those elements that have been studied in some detail, and which have a variety of geochemical properties. In addition, recognizing that many of these elements are of interest to workers who are outside the traditional stable isotope fields, we felt it was important to include discussions on the broad isotopic variations that occur in the solar system, theoretical approaches to calculating isotopic fractionations, and the variety of analytical methods that are in use. We hope, therefore, that this volume proves to be useful to not only the isotope specialist, but to others who are interested in the contributions that these non-traditional stable isotopes may make toward understanding geochemical and biological cycles. The review chapters in this volume were the basis for a two-day short course on nontraditional stable isotopes held prior (May 15-16, 2004) to the spring AGU/CGU Meeting in Montreal, Canada
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Jan 2019)
Keywords: Aufsatzsammlung; Geochemie; Isotopengeochemie; Kosmochemie; Stabiles Isotop